1998
DOI: 10.1164/ajrccm.157.6.9707011
|View full text |Cite
|
Sign up to set email alerts
|

Number and Proliferation of Basal and Parabasal Cells in Normal Human Airway Epithelium

Abstract: Two roles have been suggested for basal cells on the basis of studies performed with laboratory animals: (1) anchoring of the tracheobronchial epithelium; and (2) being the epithelial stem cell. Parabasal cells located just above the basal cells have also been shown to contribute to cell renewal. However, a systematic study of the composition and proliferation of basal and parabasal cells in normal human lungs is lacking. The aims of this study were to determine in normal human conducting-airway epithelium: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
182
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(194 citation statements)
references
References 20 publications
10
182
0
2
Order By: Relevance
“…Along with these specific features of type II pneumocytes, we detected in some cells an expression of CK 5, that in lungs has only been described in basal cells (Stosiek et al , 1992;Barth et al, 2000). Such cells are considered to be progenitor cells of bronchi and large bronchioles (Boers et al, 1998). The cuboidal alveolar cells identified in the CF pulmonary tissue may represent cells at an intermediate stage of differentiation.…”
Section: Discussionsupporting
confidence: 50%
“…Along with these specific features of type II pneumocytes, we detected in some cells an expression of CK 5, that in lungs has only been described in basal cells (Stosiek et al , 1992;Barth et al, 2000). Such cells are considered to be progenitor cells of bronchi and large bronchioles (Boers et al, 1998). The cuboidal alveolar cells identified in the CF pulmonary tissue may represent cells at an intermediate stage of differentiation.…”
Section: Discussionsupporting
confidence: 50%
“…Polarized airway epithelial cells have a relatively low rate of cell proliferation under healthy conditions, with less than 1% cell turnover. 28 Along with increased cell death, airway epithelial cell proliferation was increased in asthmatic airways as shown by increased immunopositivity for the proliferation marker MIB-1, detected with an antibody directed against part of the Ki-67 antigen (% MIB-1-positive: asthma, 19.7 Ϯ 2.5; controls, 1.8 Ϯ 0.2; Figure 2). …”
Section: Increased Apoptosis In Asthmatic Airway Epithelial Cellsmentioning
confidence: 98%
“…MIB-1, an antibody directed against recombinant parts of the Ki-67 antigen, 28 allows reliable determination of proliferating cells. 28 Endobronchial biopsies from asthmatic and control individuals were used for immunostaining.…”
Section: Immunohistochemical Analysis Of Mib-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Both basal and nonciliated se-cretory cell types of bronchial airways have been shown to exhibit proliferative capacity. 8,9,11,12,20,21,47 However, the relative contribution of secretory versus basal progenitor cell populations to epithelial maintenance and regeneration following injury remains controversial. Studies by Evans and colleagues 12 involving injury targeted to ciliated cells indicated that nonciliated secretory cells represent the preferred progenitor cell type of the bronchial epithelium.…”
mentioning
confidence: 99%